A Case of Sclerosing Epithelioid Fibrosarcoma With EWSR1 Translocation. Issue 3 (May 2017) - Imada, Hiroki; Yamaguchi, Takehiko; Iida, Shun; Ueda, Yoshihiko
Abstract : Abstract: Sclerosing epithelioid fibrosarcoma (SEF) is a rare variant of fibrosarcoma that commonly occurs in soft tissue. Since its original description in 1995, studies have revealed cytogenetic similarities with low-grade fibromyxoid sarcoma (LGFMS) and hybrid tumor composed of SEF and LGFMS. We report a case of SEF with EWSR1 gene rearrangement. A 62-year-old man had complained of a soft tissue mass in the left part of the buttock for 4 months. Imaging studies revealed a 6-cm mass in the left gluteus muscle, which was excised. Microscopically, the tumor was composed of short, spindle-shaped tumor cells with bland oval or polygonal nuclei arranged in cords and clusters with intervening sclerosing collagen matrix. Immunohistochemically, the tumor cells were positive for epithelial membrane antigen and mucin 4. Fluorescence in situ hybridization demonstrated split signals for the EWSR1 gene. These findings were consistent with SEF. Some SEFs have been reported to have shared features with LGFMS; those lesions are termed "hybrid tumors"; however, recent studies revealed that there is a pure type of SEF, which harbors EWSR1 gene rearrangements, distinct from the chromosomal abnormalities seen in LGFMS. The present case is a histologically pure SEF with EWSR1 gene translocation; its cytogenetic profile suggests that pure type SEF is a separate entity distinct from LGFMS and hybrid tumor.